'Carbon Structural Adjustment: The key to profiting from the low carbon transition' - Hargroves, Charlie; Newman, Peter (2017)
Given the imperative to respond to climate change by achieving changes to the operation of economies around the world in the coming decades, attention is now being given to possible strategic approaches including the emerging field of ‘Green Growth’ strategies. This paper begins by considering lessons from green growth strategies aimed at developing countries that may inform efforts to achieve a low carbon transition. The paper then investigates structural adjustment programs as a potential framework to extend green growth methodologies to achieve profitable low carbon transitions, and discusses the concept of ‘Carbon Structural Adjustment’. The paper concludes by presenting a road map for the development of carbon structural adjustment strategies aimed at key structural areas of the economy, implemented through strong actor and stakeholder engagement. Understanding that current progress is slower than required the paper calls for consideration of methods to increase the ‘willingness to adjust’ structures within society to achieve a low carbon transition.